2018
DOI: 10.1590/1983-1447.2017.03.58737
|View full text |Cite
|
Sign up to set email alerts
|

O sentido do cuidado espiritual na integralidade da atenção em cuidados paliativos

Abstract: RESUMO Objetivo Compreender o sentido do cuidado espiritual para a integralidade da atenção à pessoa e para a equipe interdisciplinar de cuidados paliativos. Métodos Pesquisa qualitativa com referencial teórico de Viktor Frankl. Os participantes foram nove pessoas em cuidados paliativos e seis profissionais do Programa de Internação Domiciliar Interdisciplinar que atendiam a estes. As informações foram coletadas no domicílio dos participantes, por meio da observação, e entrevistas fenomenológicas realizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
29

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 9 publications
2
12
0
29
Order By: Relevance
“…14 The relatives taking part in this study recognized that the religious environment facilitate the access to messages of Christian content, transmitted through its representatives, which Family strengths and the chemical dependence Claus MIS, Zerbetto SR, Gonçalves AMS, Galon T, Andrade LGZ, Oliveira FC provide strength, tranquility and teachings. The data corroborate study about spirituality and religiosity that shows that the messages from Sacred Books as sources of learning, comfort 15 and support to the person's change of behavior. 19 Therefore, the religious listening consists in strategies that promote calm, learning, strength to the family deal with the addiction to psychoactive substances problematic, as well as review posture and attitudes facing a moment of crisis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…14 The relatives taking part in this study recognized that the religious environment facilitate the access to messages of Christian content, transmitted through its representatives, which Family strengths and the chemical dependence Claus MIS, Zerbetto SR, Gonçalves AMS, Galon T, Andrade LGZ, Oliveira FC provide strength, tranquility and teachings. The data corroborate study about spirituality and religiosity that shows that the messages from Sacred Books as sources of learning, comfort 15 and support to the person's change of behavior. 19 Therefore, the religious listening consists in strategies that promote calm, learning, strength to the family deal with the addiction to psychoactive substances problematic, as well as review posture and attitudes facing a moment of crisis.…”
Section: Discussionsupporting
confidence: 84%
“…Studies show that praying in Christian families allows communication with God, spiritual fortification and resilience before adverse situations. 14,15 The feeling of God's presence or a Superior Being in someone's life certifies that they are not alone or helpless. 14 The frequency of this religious practice and the local that it takes place also made possible conditions to increase the family's member faith, obtain Divine mercy and have recovery expectations for the dependent relative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this category, the preoccupation with receiving the requests for religious care, respecting beliefs and values prevailed. Studies conducted with palliative care patients and health professionals have identified spiritual needs and interventions similar to those described by the participants in this study (20)(21) .…”
Section: Resultsmentioning
confidence: 93%
“…Já, os profissionais envolvidos nos cuidados paliativos afirmam que a espiritualidade torna possível um sentido para a vida, atribuindo um significado ao cuidado quando as outras possibilidades de tratamento já não existem. Na visão dos profissionais, é possível também dar sentido ao sofrimento e à morte, é uma forma de harmonizar o trabalho em equipe e trazer sentido para o mesmo (Arrieira, Thoferhn, et al, 2017).…”
Section: Espiritualidade E Cuidados Paliativosunclassified